1996
DOI: 10.1097/00000539-199604000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Prior Hypothermia Attenuates Malignant Hyperthermia in Susceptible Swine

Abstract: This study was designed to determine the extent by which mild or moderate hyperthermia attenuates the triggering of malignant hypothermia (MH) induced by the combined administration of halothane and succinylcholine. Sixteen susceptible swine were initially anesthetized with nontriggering drugs and then either kept normothermic (approximately equal to 38 degrees C, n = 6) or cooled to induce mild (approximately equal to 35 degrees C, n = 6), or moderate (approximately equal to 33 degrees C, n = 4) hypothermia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
4

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 9 publications
0
10
0
4
Order By: Relevance
“…La hipotermia posee efecto directo sobre la inmunidad celular y humoral 50,52 y efecto indirecto a través de la disminución de la oferta de O2 a los tejidos periféricos 76,77 . La disminución de 1,9 o C en la temperatura central triplica la incidencia de infección en el local de la operación después de resección del colon y aumenta en 20% la duración de la hospitalización, lo que también genera aumento del costo hospitalar.…”
Section: Sistema Inmunológicounclassified
See 1 more Smart Citation
“…La hipotermia posee efecto directo sobre la inmunidad celular y humoral 50,52 y efecto indirecto a través de la disminución de la oferta de O2 a los tejidos periféricos 76,77 . La disminución de 1,9 o C en la temperatura central triplica la incidencia de infección en el local de la operación después de resección del colon y aumenta en 20% la duración de la hospitalización, lo que también genera aumento del costo hospitalar.…”
Section: Sistema Inmunológicounclassified
“…Un estudio experimental demostró menor incidencia de HM en pacientes susceptibles sometidos a hipotermia, bien como menor gravedad de las crisis una vez desencadenadas 77 .…”
Section: Otros Beneficiosunclassified
“…However, the clinical presentations and first signs of MH episode are highly variable, especially when some individuals exhibit only one or a few symptoms of varying intensity; it is not easy to diagnose MH with confidence [31,32]. Although the underlying causes for the variability of the clinical presentation are poorly understood, different potency, concentration and duration of exposure to the triggering inhalation anesthetics, as well as additional factors, such as temperature, age and genetic variability, may be related with the heterogeneous clinical presentations [31,33,34]. The variability in the order and time of onset of signs often makes the clinical diagnosis rather difficult [7,35,36].…”
Section: Clinical Presentation and Diagnosismentioning
confidence: 99%
“…The underlying causes for the variability of the clinical picture have not yet been identified. Varying potency, concentration and duration of exposure to the trigger, as well as additional factors such as temperature [68,69], age and genetic variability [70], might explain the heterogeneous picture.…”
Section: Clinical Symptoms and Treatmentmentioning
confidence: 99%
“…On the contrary, MHN swine did not show any reaction at all. Iaizzo and his colleagues demonstrated that mild hypothermia had a harmful influence on the onset and extent of the syndrome whereas moderate hypothermia even prevented MH induction with halothane and succinylcholine [69]. After rewarming, MH could be triggered by the same drugs.…”
Section: Stress and Temperaturementioning
confidence: 99%